Jeju Island Geopark - A Volcanic Wonder of Korea - Woo, Kyung Sik. (Geoparks of the World (closed), Development and Management,, 2013)
This book will deal with geological as well as cultural, historical, archaeological and biological aspects in Jeju Global Geopark. It will start with introduction of Jeju Global Geopark, geographic setting, habitats, history, economy and tourism, management, general geology and geosites, future geosites, other significant heritage sites, economically sustainable tourism, education and promotion and management plan.